Studies on domestication of two species of wild edible mushroom from Brazil - Drewinski, Mariana de Paula; Corrêa-Santos, Marina P.; Zied, Diego C. [UNESP]; Menolli, Nelson (FapUNIFESP (SciELO), 2024)
There are about 80 species of wild edible mushroom that certainly occur in Brazil and can be used as a natural source of food and medicine. This study aimed to evaluate the in vitro mycelial development in culture media at different temperatures and substrates for cultivation of the edible mushroom species Auricularia fuscosuccinea and Laetiporus gilbertsonii. Additionally, the cultivation and the nutritional composition of A. fuscosuccinea mushrooms were evaluated. The two best wild strains of each species were selected for the in vitro cultivation experiment in two different substrates. Furthermore, an axenic cultivation on sawdust was conduct and the basidiomata produced were evaluated on their nutritional composition. The temperatures that best favored the mycelial growth were 30 °C for A. fuscosuccinea and 25 °C and 30 °C for L. gilbertsonii. The mycelium of both species developed better in the sterile Eucalyptus sawdust substrate. Despite the success in cultivating the mycelium of L. gilbertsonii, it was not possible to obtain basidioma for this species. On the other hand, it was possible to produce basidiomata of the two tested wild strains of A. fuscosuccinea.
Keywords: Atlantic Rainforest; Auricularia fuscosuccinea; Laetiporus gilbertsonii; mushroom cultivation; nutritional content